2016
DOI: 10.1016/j.rboe.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility assessment of different descriptions of the Kellgren and Lawrence classification for osteoarthritis of the knee

Abstract: ObjectiveTo assess the inter- and intraobserver reproducibility of the original version and different descriptions of the Kellgren and Lawrence classification used in epidemiological studies for osteoarthritis of the knee.MethodsThe study included 72 patients with osteoarthritis of the knee. Three medical members of the Brazilian Society of Knee Surgery were invited to evaluate the images. An intra- and interobserver analysis was conducted, with an interval of one month. The intraobserver agreement was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
4
0
2
Order By: Relevance
“…Comparable to other studies on ROA, we included them in our analysis to avoid inflation of incidence and progression rates 20 . Despite these limitations, our results are comparable to the estimates from other well-known cohort studies, which gives us confidence that, in most cases, our results are reliable 5,27,28 .…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Comparable to other studies on ROA, we included them in our analysis to avoid inflation of incidence and progression rates 20 . Despite these limitations, our results are comparable to the estimates from other well-known cohort studies, which gives us confidence that, in most cases, our results are reliable 5,27,28 .…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Although widely used by orthopedists and radiologists, the subjective component of KL classification has been mentioned in previous literature. 6 Therefore, it is essential to develop a KL classification model with good interobserver agreement compared with physicians. We merged the KL 0 and 1 classes based on the finding that both represent no radiographic evidence of OA change.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Gonçalves et al. while reporting on reliability testing for grading of OA using the KL method showed conflicting results [3]. The study reported that the level of agreement in the inter observer analysis was superficial.…”
Section: Introductionmentioning
confidence: 99%
“…Although Kellgren and Lawrence (KL) method is the most commonly used grading system for knee OA, however, it has poor objectivity [2]. In a recent study, Gonçalves et al while reporting on reliability testing for grading of OA using the KL method showed conflicting results [3]. The study reported that the level of agreement in the inter observer analysis was superficial.…”
Section: Introductionmentioning
confidence: 99%